Analisis Break Even Point pada UMKM “Tengteng Mamah Mimin” Desa Jayamulya Kabupaten Karawang - Alsa Dyah Tania; Reminta Limban Batu (Universitas Batanghari Jambi, 2022)
UMKM Tengteng Mamah Mimin are UMKM engaged in processed food with a manufacturing process using traditional methods. The purpose of this study is to determine the costs incurred, the number of products sold, and the profit and loss obtained. The amount of profit and loss obtained is a benchmark for the success of the business being run. In this study, it used Break Even Point (BEP) analysis as a tool to test business feasibility and find out the break-even point. By knowing the break-even point of UMKM Tengteng Mamah Mimin can plan the profit target you want to get. In this study, the author conducted a direct interview with UMKM business owner Tengteng Mamah Mimin. The result of this analysis is the fixed cost of its production which is Rp 168,000 and the variable cost for production which is Rp 1,456,000. UMKM Tengteng Mamah Mimin can produce 2.000 tengteng every day and with a selling price of Rp 2,500 per unit.